COMPARATIVE RESULTS IN GUMMY SMILE TREATMENT WITH TWO DIFFERENT TYPES OF THERAPY - Rezk Gavrilă Taalat Gabriel; Anamaria Bechir; Edwin Sever Bechir (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study The aim of this study was to compare the results of the treatment of the gingival smile by two techniques, Botox injection (in the first group of patients) and laser therapy (the second group of patients). Materials and methods The study included 30 female patients diagnosed with anterior gummy smile, aged of 31 and 45, who were separated into two groups. The first group of 15 patients was injected with Botox (Allergan), and second group of patients received laser therapy (Fotona LightWalker Laser). A questionnaires with four parts was used, which contained: demographic data; the degree of pain intensity after the intervention; the patient satisfaction degree according to the applied therapy; the degree of changes in patients' life quality after the applied treatment. Results On the fourth day after the interventions (the first follow-up session), the degree of pain intensity in the patients with laser gingivectomy was much higher than in the patients injected with Botox. The satisfaction of patients with gummy smiles who were treated with Botox therapy was the highest at all monitoring sessions, in contrast to the satisfaction of patients with laser therapy, which was above average to maximum at all monitoring sessions. The quality of life of the patients was greatly increased in both groups. Conclusions The impact of both therapies on the treatment of gummy smiles was beneficial. The aesthetics and psychological well-being increased after the applied therapies.